Comparative assessment of the environmental hazards of and exposure to perfluoroalkyl phosphonic and phosphinic acids (PFPAs and PFPiAs): Current knowledge, gaps, challenges and research needs. (April 2016) - Wang, Zhanyun; Cousins, Ian T.; Berger, Urs; Hungerbühler, Konrad; Scheringer, Martin
Abstract: Perfluoroalkyl phosphonic and phosphinic acids (PFPAs and PFPiAs) are sub-groups of per- and polyfluoroalkyl substances (PFASs) that have been commercialized since the 1970s, particularly as defoamers in pesticide formulations and wetting agents in consumer products. Recently, C4 /C4 PFPiA and its derivatives have been presented as alternatives to long-chain PFASs in certain applications. In this study, we systematically assess the publicly available information on the hazardous properties, occurrence, and exposure routes of PFPAs and PFPiAs, and make comparisons to the corresponding properties of their better-known carboxylic and sulfonic acid analogs (i.e. PFCAs and PFSAs). This comparative assessment indicates that [i] PFPAs likely have high persistence and long-range transport potential; [ii] PFPiAs may transform to PFPAs (and possibly PFCAs) in the environment and biota; [iii] certain PFPAs and PFPiAs can only be slowly eliminated from rainbow trout and rats, similarly to long-chain PFCAs and PFSAs; [iv] PFPAs and PFPiAs have modes-of-action that are both similar to, and different from, those of PFCAs and PFSAs; and [v] the measured levels of PFPAs/PFPiAs in the global environment and biota appear to be low in comparison to PFCAs and PFSAs, suggesting, for the time being, low risks from PFPAs and PFPiAs alone. Although risks from individual PFPAs/PFPiAs are currently low, their ongoing production and use and high persistence will lead to increasing exposure and risks over time. Furthermore, simultaneous exposure to PFPAs, PFPiAs and other PFASs may result in additive effects necessitating cumulative risk assessments. To facilitate effective future research, we highlight possible strategies to overcome sampling and analytical challenges. Highlights: This is a first thorough environmental assessment of PFPAs and PFPiAs. PFPAs likely have high persistence and long-range transport potential. PFPiAs may transform to PFPAs and possibly PFCAs in the environment and biota. PFPAs/PFPiAs have similar environmental and human exposure routes to other PFAAs. Simultaneous exposure to PFPAs/PFPiAs and other PFAAs may cause additive effects.